HRM practices and employees turnover intention of private higher education institutes (pheis) in Penang: the mediating roles of workplace Well-being - Koay, Lian San (2010)

(untitled)
Tujuan kajian ini adalah untuk menyelidik factor-factor yang mempengaruhi amalanamalan HRM terhadap niat pertukaran kerja di antara ahli akademik Lembaga Pendidikan Tinggi Swasta (PHEIs) di Penang.